The use of Chinese adverbs 又 (yòu) and 再(zài) by Indonesian students: error analysis - Arini Junaeny; Mir'ah Azizah (Politeknik Negeri Bali, 2022)
This study aims to obtain data and analysis of errors in the use of adverbial words 又 (yòu) and 再(zài) in Chinese Language Education Study Program students and the factors that influence Chinese learners' errors in the use of structures. The adverbial words 又 (yòu) and 再(zài)in the Chinese Language have their structure in use. It is very important to learn and understand. Chinese language learners often make mistakes in using these two words. This study uses a qualitative approach with data sources from the results of student tests and secondary data from open questionnaires. From the data, the percentage of errors in the use of the adverbial (yòu) was 32.49% and the use of the adverbial (zài) was 29.49%. And from the results of making sentences, it was found that the forms of errors were, the use of 又 (yòu) in sentences, the use of 再 (zài) in sentences, sentence structure, use of vocabulary, and sentence logical meaning, with a total of 25 errors.